Parent Coach: The Utilization Of The Score Model For Children’s Cognitive, Affective, And Conative Development - Geofakta RAZALI; Wulan FURRIE; Alo LILIWERI; Alexander SERAN (International Journal of Environmental, Sustainability, and Social Science, 2023)
Communication that does not run smoothly will cause miscommunication. In family communication that is carried out between parents and children, if miscommunication is not immediately resolved, there will be communication congestion. One way to solve this problem is through coaching. In this case, parents become a coach for their children, which is called a "parent coach," by using the SCORE model. This study aims to improve communication skills for parents and strengthen children's cognitive, affective, and communicative abilities. This study uses a qualitative research method with a case study approach. The results show that through communication based on family coaching and utilizing the score model, parents have good questioning skills so as to produce optimal performance as parents and provide opportunities for children to provide feedback to parents. and parents are trained to be good listeners. With a series of actions taken by parents through coaching sessions, parents can find out the values of life that are considered "valuable" for children.